PENGARUH APLIKASI FDC DAN KUALITAS LAYANAN TERHADAP PRODUKTIVITAS KARYAWAN YANG DIMEDIASI OLEH KEPUASAN PASIEN - Nurmelinda; Suharto; Muhammad Harri (Jurnal Ekonomi dan Industri, 2025)
This research aims to test and analyze 1). the influence of applications on employee productivity directly; 2). The direct influence of service quality on employee productivity; 3). Indirect influence of application on patient satisfaction; 4). Indirect influence of service quality on patient satisfaction; 5). The influence of applications and service quality on employee productivity; 6). The influence of applications and service quality on employee productivity through patient satisfaction. Research was conducted on FDC dental clinic employees with a research sample of 60 respondents. The sampling technique uses simple random sampling technique. The data analysis method uses descriptive analysis and regression analysis. The research results show that: 1). There is an influence of applications on employee productivity; 2). There is an influence of service quality on employee productivity; 3). There is an influence of the application on patient satisfaction; 4). There is an influence of service quality on patient satisfaction; 5). There is an influence of patient satisfaction on employee productivity; 6). There is an influence of applications and service quality on employee productivity